Molecular Mechanisms of Gynostemma pentaphyllum in Prevention and Treatment of Non-Small-Cell Lung Cancer. (6th September 2022) - Liang, Renji; Wu, Jinzheng; Lin, Ronghua; Ran, Liling; Shu, Bo; Deng, Hao
Abstract : Objective . Lung cancer represents the leading cause of cancer death on a global scale. Gynostemma pentaphyllum ( G. pentaphyllum ), a traditional medicinal material with a high medicinal and health value, has recently been reported for its anticancer activity. However, the pharmacological mechanism of G. pentaphyllum in non-small-cell lung cancer (NSCLC) remains to be elucidated. Methods . The active ingredients of G. pentaphyllum were obtained from the TCMSP database and known therapeutic targets of NSCLC from the GeneCards and OMIM databases. Disease-drug common targets are subjected to protein-protein interaction (PPI), GO enrichment analysis, and KEGG pathway enrichment analysis. A molecular docking strategy was performed to verify the interaction between molecules. Results . We found a total of 24 compounds of G. pentaphyllum fulfilling OB ≥ 30% concomitant with DL ≥ 0.18 and corresponding 81 target genes in the TCMSP database, with 5062 NSCLC-related genes collected in the GeneCards and OMIM databases. The network consisting of the disease-target compound was obtained, including 8 active ingredients and 69 common targets. The PPI network with 65 nodes and 645 edges was visualized. After functional enrichment analysis, it was revealed that the therapeutic effects of G. pentaphyllum on NSCLC were achieved through response to ketone, gland development, and cellular response to xenobiotic stimulus. After molecular docking analysis, it was revealed that the two active ingredients of G. pentaphyllum, quercetin and rhamnazin, bound well and stably to their targets (MYC, ESR1, and HIF1A). Conclusion . Our study, based on network pharmacology, identifies active ingredients, targets, and pathways model mechanism of G. pentaphyllum when it is used to treat NSCLC.